Functionality; productivity; and challenges of land redistribution in Ehlanzeni Region of Mpumalanga Province : a case study of Mbombela Local Municipality with reference to Lahlamali Community Property Association - Mabuza, Mandla Elias (My University, 2014)
The legacy of apartheid has left the current democratic government of South Africa grappling with vast challenges. Eighteen years of governance has not been enough for the state to address issues of land redistribution, and in particular redistribution of commercial farm and the improvement of their functionality after redistribution. The main aim of the study is to assess the general functionality, productivity and challenges of redistributed farms. Qualitative research methodology (descriptive research design) is used to diagnose historical and current issues impacting on the functionality, productivity and challenges facing LCPA. Probability random sampling, more especially stratified random sampling was used as a sampling method. The results indicated that the farm is experiencing a number of challenges, conflicting views regarding the farm path. Due to the lack of financial support, malfunctioning or aging infrastructure, and most importantly the lack of agricultural technical and farming knowledge. Challenges experienced among others include the following, consistent decline in production, lack of technical and strong agricultural farming knowledge, lack of persistent strong financial support; and lack of integrated support from agricultural stakeholders. To change the status quo, consistent training of beneficiaries in farming and farm management has to be tailor made for them, and a multidimensional support for beneficiaries has to be put in place.
Thesis (M. Dev. ) --University of Limpopo, 2014
Keywords: Land redistribution; 333.31096827; Land reform -- South Africa -- Mpumalanga; Farms -- South Africa -- Mpumalanga